Pelatihan Penyusunan Soal Kurikulum Merdeka Untuk Meningkatkan Kompetensi Guru - Indra Kurniawan; Andri Rahadyan (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
The independent learning curriculum offers a learning concept, namely freedom to think, freedom to innovate, freedom to learn independently and creatively. This community service activity aims to improve the ability of HSPG Bekasi teachers regarding preparing independent curriculum questions. Implementation of community service is carried out through several stages such as assessment, planning and development, implementation (socialization), and evaluation. The number of participants was around 20 HSPG Bekasi teachers. Based on these results, information was obtained that this activity was very relevant to the participants' needs. This activity increases knowledge and skills regarding preparing independent curriculum questions. If it is made in the form of a percentage increase from the initial ability of 50%, after training the understanding becomes more than 85%.